Synthesis of Biodegradable Multiblock Copolymers by Click Coupling of RAFT-Generated HeterotelechelicPolyHPMA Conjugates - Yang, Jiyuan (2011)
A new strategy for the synthesis of biodegradable high molecular weight N-(2-hydroxypropyl)methacrylamide (HPMA)-based polymeric carriers has been designed. An enzyme-sensitive, alkyne-functionalized, chain transfer agent (CTA-GFLG-alkyne; N(α)-(4-pentynoyl)-N(δ)-(4-cyano-4-(phenylcarbonothioylthio)pentanoyl-glycylphenylalanylleucylglycyl)-lysine) was synthesized and used to mediate the reversible addition-fragmentation chain-transfer (RAFT) polymerization and copolymerization of HPMA. Post-polymerization modification with 4,4′-azobis(azidopropyl 4-cyanopentanoate)resulted in the formation of heterotelechelic HPMA copolymers containing terminal alkyne and azide groups. Chain extension via click reaction resulted in high molecular weight multiblock copolymers. Upon exposure to papain, these copolymers degraded into the initial blocks. Similar results were obtained for copolymers of HPMA with N-methacryloylglycylphenylalanylleucylglycyl thiazolidine-2-thione and N-methacryloylglycylphenylalanylleucylglycyl-gemcitabine. The new synthetic method presented permits the synthesis of biocompatible, biodegradable high molecular weight HPMA copolymer-anticancer drug conjugates that possess long-circulation times and augmented accumulation in solid tumor tissue due to the enhanced permeability and retention effect.